International Experience of State Governance in the Field of Environmental Rotection and Rational Environmental Consumption - Pugach, Andriy; Marenichenko, Valerii (Pressing Problems of Public Administration, 2019)
The international experience of environmental protection and rational use of natural resources in the perspective of national programs is researched. In particular, the National Programs have been identi ed: USA The US Wetlands Action Plan (US Fish & Wildlife Service, 1990), The US Environment Protection Agency and Army Corps of Engineers (Lynch-Stewart, 1992); Netherlands – Danish “no loss” wetlands policy (Moller, 1995); EU – European Union principles for the implementing a no net loss policy (Commission of the European Communities, 1995). Environmental agreements as an instrument of state governance in the  eld of environmental protection have been identi ed. In particular, the agreements that cover different problem areas, such as reducing the environmental impact of existing sources pollution, reduction of toxic substances, the content of harmful substances in products, to prevent the formation and recycling of waste and others are dened. The basic forms of industrial self-regulation in the  eld of environmental policy are determined. In particular, there is de nition that the standard form of self-regulation of industry in the  eld of environmental policy is self-commitments, not formal agreements in Germany. The legal regulation of environmental protection of EU countries is analyzed. In particular, it is determined that in the laws of European countries environmental protection is considered as an integral part of socio-economic policy, but the priority in the protection of certain natural objects is different. The priority measures in the international practice of environmental protection and rational use of natural resources are substantiated. In particular, it should be highlighted among them, such as the introduction of a mechanism for the decommissioning of public debt in exchange for environmental improvements (“nature debts”); creation of model centers of balanced development with international status; setting a strict ban on  nancing new mining projects in areas where local people are opposed to such projects.